Comparison of treatment results of urinary incontinence verified/or not verified with urodinamic evaluation by using UDI-6, IIQ-7 questionnaire forms - Okuyan, Erhan; Cakir, Caner; Gunakan, Emre; Ozkaya, Enis; Kucukozkan, Tuncay; Sefik Ozyurek, Eser (Annals of Medical Research, 2021)
Aim: Treatment of mixed type incontinence includes surgical and/or medical options. The efficacy of treatment frequently depends on the patient based choice. Thus, we aimed to compare treatment efficacy with UDI-6 and IIQ-7 questionnaire forms in groups with/without urodynamics in the diagnosis of mixed type incontinence.Material and Methods: In our study, 60 patients were registered. Patients were evaluated in 2 groups including 30 patients that: agreed (Group 1) to and did not agree (Group 2) for a urodynamic exam. "Quality of life" scoring questionnaires, urodynamics records, and urethral angle measurements were performed in both groups. Patients in the groups were evaluated in subgroups whether they received TOT (Transobturator tape) and/or medical treatment. Group 1; A: TOT patients, B: TOT + medical treatment, C: Only medical treatment; Group 2; D: TOT + medical treatment, E: Only medical treatment. Results: The mean age of the patients was 49 and 70% of patients were postmenopausal. Most of the patients were obese 45% of patients had had a BMI of >40kg/m2. The rate of TOT received the patients in Group 1 and 2 were 21 (70%) and 13 (43.3%), respectively. An analysis of questionnaire scores %94.4 of all patients stated a regression in symptoms after treatment. Both surveys showed positive changes in all groups. The change ratio in the survey scores was 81.1% and 67.3% in Group 1 and 2 respectively in UDI- 6 survey similarly with IIQ-7 survey results as 81.1% and 63.5 % in Group 1 and 2 respectively. In the comparison of medical treatment subgroups (C and E) the change rate was significantly lower in patients who did not agree with urodynamic in UDI 6 and IIQ7 surveys ( 86.4% vs 55.0%, p.001 and 79.7% vs. 50.5%, p0.001.Conclusion: Although it is limited in urge type dominant incontinence patients, non-complex UI patients benefit from appropriate treatment regardless of urodynamics evaluation. In the management of UI patients' QoL questionnaires before and after treatment might be helpful.
Keywords: Mixed type incontinence; quality of life form; urodynamics